Photocatalytic Water Splitting: Toward a Future of Hydrogen Energy - Dusyant (Journal of Science in Medicine and Life, 2024)
Photocatalytic water splitting is a promising technology for sustainable hydrogen production using solar energy. This paper provides a comprehensive review of recent advancements in photocatalytic water splitting, including the development of new photocatalysts, improvements in reaction efficiency, and challenges faced in practical applications. The study explores the mechanisms of photocatalysis, evaluates different photocatalytic materials, and discusses the future directions of this technology for large-scale hydrogen energy production.